Analisis Pengendalian Kualitas pada Purified Gypsum Menggunakan Metode Six Sigma (DMAI) di PT. Petrokimia Gresik - Moh Galih Rachmat Aditya; Efta Dhartikasari Priyana; Yanuar Pandu Negoro (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. Petrokimia Gresik is a fertilizer and non-fertilizers producing company. Purified gypsum is a by-product of the production of Phosphoric Acid, which is used as a mixture in cement products. As production activities progress, there are producing results that have poor quality/defects, therefore we analyze to find the factors that cause product defects. The method used is the Six Sigma (DMAI) method which starts by calculating the DPMO value and determining the Sigma Level against two predetermined key parameters, namely Crystal H2O and CaSO4.2H2O. The data used are historical data from purified gypsum analysis in April 2022 and data from brainstorming with several production operators. After calculations for Crystal H2O levels, DPMO values of 263,420 and Sigma levels of 2.24 were obtained. For CaSO4. 2H2O obtained a DPMO value of 285,921 and a Sigma Level of 2.21. Based on these results, PT. Petrokimia Gresik has process capabilities below the company standards set in Indonesia with a Level Sigma of 3.4. The cause of defective products due to reactions in reactors that have not been maximized because the incoming raw materials have poor quality. Filter cloth is saturated due to poor quality. The difficulty of control in the field is due to the uneven quality of raw materials.